ISOLATION AND ANTIBACTERIAL ACTIVITY OF ENDOPHYTIC MOLD FROM DAHLIA TUBER PLANTS (Dahlia variabilis) AGAINST Stapylococcus aureus and Stenotrophomonasmaltophilia strainW1-2 - Diki, Muhammad; Rita Permatasari; Dewi Yudiana Shinta; Mohd Fadly Md Ahid; Evana Kamarudin (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Antibiotic resistance to pathogenic bacteria has developed in a short period of time and is faster than has been thought. Therefore, it is necessary to find new antibiotic alternatives that are sourced from natural materials such as endophytic molds of dahlia tubers. This study was conducted to test the antibacterial activity of endophytic molds isolated from dahlia bulbs against Staphylococcus aureus and Stenotrophomonasmaltophilia strain W1-2. The results of the selection of antimicrobial activity of endophytic mold isolated from the dahlia tuber were fermented using the shaking method on Potato Dextrose Broth medium. The results of fermentation are tested for antibacterial activity using the disc diffusion method. Of the 10 isolated endophytic molds, two isolates with antibacterial activity were obtained, namely A-1 and A-7 isolates. The results of the antibacterial activity test of A-1 isolate against Staphylococcus aureus bacteria had the highest inhibition zone of 32.75 mm and Stenotrophomonasmaltophilia strain W1-2 had the highest inhibition zone of 19.25 mm. In A-7 isolate against Staphylococcus aureus bacteria had the highest inhibition zone of 29.5 mm and against Stenotrophomonasmaltophilia strain W1-2 had the highest inhibition zone of 15.25 mm. Based on the results of the antibacterial activity test carried out by the isolate, the isolate mold isolates with codes A-1 and A-7 have the highest antibacterial activity against Staphylococcus aureus and have a strong inhibitory power against Stenotrophomonasmaltophilia strain W1-2. The results showed that molds A-1 and A-7 had the potential to be antibacterial agents and GC-MS analysis of antibiotic compounds detected by hexanorlabdane. Molecular identification using the ITS gene observed that the A-1 mold isolate was 100% similar to the genomic2011f6MT558940.1 strain of Aspergillus Fumigatus